Relief influence on tree species richness in secondary forest fragments of Atlantic Forest, SE, Brazil - Silva, William Goulart Da; Metzger, Jean Paul; Bernacci, Luis Carlos; Catharino, Eduardo Luís Martins; Durigan, Giselda; Simões, Sílvio (Sociedade Botânica do Brasil, 2008)
The aim of this work was to explore the relationship between tree species richness and morphological characteristics of relief at the Ibiúna Plateau (SE Brazil). We sampled 61 plots of 0.30 ha, systematically established in 20 fragments of secondary forest (2-274 ha) and in three areas within a continuous secondary forest site, Morro Grande Reserve (9,400 ha). At each plot, 100 trees with diameter at breast height > 5 cm were sampled by the point centered quarter method, and total richness and richness per dispersal and succession class were obtained. The relief was characterized by the mean and variance of slope, elevation, aspect and slope location. There was no significant relationship between relief heterogeneity and tree species richness. Relief parameters generally did not affect tree richness, but elevation was particularly important especially in the continuous forest. Despite the limited range of altitudinal variation (150 m), species richness increases with elevation. The highest areas were also those with the largest forest cover and the lowest disturbance degree, which should contribute to the greater richness of those sites. Our results suggest an indirect influence of relief, due to the fact that deforestation is less intense in higher regions, rather than a direct influence of abiotic factors related to the altitudinal gradient.

O objetivo deste trabalho foi explorar a relação entre a riqueza de espécies arbóreas com as características morfológicas do relevo no Planalto de Ibiúna (SE, Brasil). Foram amostrados 61 blocos de 0,30 ha, sistematicamente estabelecidos em 20 fragmentos de floresta secundária (2-274 ha) e em três áreas de uma floresta secundária contínua, a Reserva do Morro Grande (9.400 ha). Em cada bloco, 100 árvores com diâmetro à altura do peito > 5 cm foram amostradas pelo método do quadrante centrado, e as riquezas total e por grupo de dispersão e sucessão foram obtidas. O relevo foi caracterizado pela média e variância da declividade, altitude, orientação e posição na vertente. Não houve relação significativa entre a heterogeneidade do relevo e a riqueza de espécies arbóreas. Os parâmetros do relevo afetaram pouco a riqueza da vegetação, mas a altitude foi particularmente importante, especialmente na floresta contínua. Apesar da pouca extensão na variação de altitude (150 m), a riqueza aumentou com este fator. As áreas mais altas também foram aquelas com as maiores coberturas florestais e os mais baixos graus de perturbação, o que deve contribuir para a maior riqueza dessas áreas. Nossos resultados indicam uma influência indireta do relevo, pelo fato das áreas mais altas serem também as menos desmatadas, e não uma influência direta de fatores abióticos relacionados ao gradiente de altitude.
Influência do relevo na riqueza de espécies arbóreas em fragmentos de floresta secundária de Mata Atlântica, SE, Brasil
Keywords: relief; tree species richness and composition; Atlantic Forest; land use; relevo; riqueza e composição de espécies arbóreas; Mata Atlântica; uso da terra